Detecção imunoistoquímica de receptores de estrógeno e progesterona no endométrio de vacas Nelore (Bos taurus indicus) durante o anestro pós-parto - Lima, Rafaela Sanches; Martin, Ian; Marques Filho, Wolff Camargo; Rodrigues, Marcela Marcondes P.; Amorin, Renee Laufer; Ferreira, João Carlos Pinheiro [UNESP] (My University, 2011)
Twenty-four postpartum anestrous Nelore purebred cows were used in the study. Anestrous was determined based on the reproductive history which was confirmed in each cow based on plasma progesterone concentration and by transrectal ultrasonography. Endometrial biopsies were collected. The animals were separated into two groups according to maximum follicular diameter- Group 1: follicles <6mm (n=12) and Group 2: follicles >-6mm follicles (n=12). The immunohistochemistry technique was employed to evaluate the presence of estrogen and progesterone receptors in the uterine glandular epithelium and stroma. High counts of positive nuclei and high intensity of immunostain for estrogen and progesterone receptors in the glandular epithelium and stroma were observed in the two groups. However, the immunostain intensity of progesterone receptors in the glandular epithelium was higher in Group 2 compared to Group 1. When glandular epithelium and stroma were compared within each group, the relative number of estrogen receptors in the Group 1 was higher in the glandular epithelium compared to stroma and the immunostain intensity for the progesterone receptor in Group 2 was higher in the glandular epithelium compared to stroma. The results suggest that the mechanisms that control the expression of endomerial receptors in the anestrus are similar to the ones observed during the estrus cycle.

Foram utilizadas 24 vacas Nelore P.O., em anestro pós-parto, diagnosticado pelo histórico reprodutivo, por avaliações ultrassonográficas transretais e por dosagem de progesterona plasmática, que foram submetidas à colheita de fragmento uterino via transcervical. Os animais foram divididos em dois grupos conforme o máximo diâmetro folicular: grupo 1: folículos <6mm (n=12); grupo 2: folículos >6mm (n=12). Para avaliar receptor de estrógeno e receptor de progesterona no epitélio glandular e no estroma, foi utilizada a técnica de imunoistoquímica. Altas contagens relativas e alta intensidade de marcação para receptor de estrógeno e progesterona no epitélio glandular e no estroma foram observadas nos dois grupos. No entanto, a intensidade de marcação para o receptor de progesterona no epitélio glandular foi mais alta no grupo 2 comparado ao grupo 1. Quando o epitélio glandular e o estroma foram comparados, o número relativo de receptor de estrógeno no grupo 1 foi mais alto no epitélio glandular comparado ao estroma, e a intensidade de marcação para o receptor de progesterona no grupo 2 foi mais alta no epitélio glandular comparado ao estroma. Os resultados sugerem que os mecanismos que controlam a expressão de receptores no anestro são semelhantes aos observados durante o ciclo estral.
Immunohistochemical detection of receptors for estrogen and progesterone in endometrial glands and stroma during the pospartum anestrus in Nelore (Bos taurus indicus) cows
Keywords: Nelore; Endometrium; Steroidal receptor; Nelore; Endométrio; Receptores esteroidais